Extended genetic analysis of Brazilian isolates of Bacillus cereus and Bacillus thuringiensis - Zahner, Viviane (2013)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Setor de Entomologia Médica Forense. Laboratório de Transmissores de Leishmanioses. Rio de Janeiro, RJ, Brasil.